Effect of cationic order-disorder on the transport properties of LaBaCo2O6-d and La0.5Ba0.5CoO3-d perovskites - Garcés, Diana Andrea (2014)
A-site cationic ordered LaBaCo2O6-d and disordered La0.5Ba0.5CoO3-d, perovskite phases were obtained by Solid State Reaction. Their structural properties were studied at room temperature and 400 °C combining powder diffraction techniques, XRD and NPD with an independent determination of the oxygen content of the samples by thermogravimetry. La0.5Ba0.5CoO3-d exhibits cubic symmetry with cations randomly distributed, whereas the LaBaCo2O6-d shows tetragonal symmetry with the La+3 and Ba+2 ions distributed in alternating layers. The diffraction data were analyzed using the Rietveld method and testing different structural and microstructural models. Bond Valence and Fourier methods were used to determine bond distances and neutron/electron density maps. The LaBaCo2O6-d presents higher concentration of oxygen vacancies than La0.5Ba0.5CoO3-d, because the O is weakly bonded to LaO layers. The anisotropic atomic displacement and the neutron density distribution suggest a two-dimensional O-migration path for LaBaCo2O6-d and a three-dimensional for La0.5Ba0.5CoO3-d.The mechanism of electrical conductivity is by electron-hole with high mobilities (La0.5Ba0.5CoO3−d= 2.49 cm2V−1s−1and LaBaCo2O6−δ= 1.48 cm2V−1s−1 at room temperature) and low activation energy (26−=0.019 and 0.50.53−=0.030 ). It has been also found that the higher electronic and ionic conductivities in La0.5Ba0.5CoO3-d compared to those in LaBaCo2O6-d, is due to the higher dimensionality of transport and to higher overlapping between Co-3d and O-2p orbital.